KARAKTERISTIK SELEBRITIS SEBAGAI MODEL IKLAN DAN PERANNYA TERHADAP NIAT BELI PRODUK SEPEDA MOTOR YAMAHA PADA MAHASISWA STIE PERBANAS SURABAYA - Abdurrahman M; Herizon . (STIE Perbanas Surabaya, 2011)
This research is a form of causal research that is aimed to identify the causal effects of independent variable such as attractiveness, expertise, trustworthiness towards the purchase intention variable with the respondents of the students at STIE Perbanas Surabaya. This study attempts to test the hypothesis by giving questionnaires to the students. The sampling is non probability sampling and the data analysis technique is descriptive statistics. Confirmatory factor analysis is done by structural equation models (SEM) with Amos 16. It shows as the following. First, attractiveness has no influence towards the purchase intention. This means that attractiveness of the advertising model does not influence the potential customers purchase intention to buy the products supported by the advertising model. Second, expertise has no influence either towards the purchase intention. This also means that expertise of advertising model has no effect on supporting the products being advertised and has no effect either on purchase intention toward product by the potential customers. Finally, trustworthiness has positively significant influence towards the purchase intention, this means that the higher level of trustworthiness in potential customer with the advertising model will increase the prospect of potential customer purchases intention to buy the products being supported.